Academics pan MP’s ‘half-baked’ idea of Mitra-like unit for Dayaks - FMT Reporters (2025)
Academics, Jayum Jawan & Madeline Berma commented on suggestiuon of having MITRA-liked unit for the Dayaks in Sarawak.